EFFECTS OF CORIOLIS FORCE ON CURRENT AND SUSPENDED SEDIMENT TRANSPORT IN THE COASTAL ZONE OF RED RIVER DELTA - Vinh, Vu Duy; Ouillon, Sylvain (Vietnam Journal of Marine Science and Technology, 2014)
This paper presents some results of three dimensional (3D) modelling application to research effects of Coriolis force on field current and suspended sediment transport in the coastal area of Red River delta. In this study, a 3D numerical model was set up, calibrated and validated by measured data. Two simulation groups were set up: with Coriolis force and without Coriolis force in the model. The studied results show that the Coriolis force is factor, which causes and strengthens flows alongshore, increases current velocity in coastal zone of Van Ly - Hai Hau. This factor also increases alongshore water and suspended sediment flux from north to southwest with the variation in each cross sections. The results have also shown the role of Coriolis force on the lack of sediment in coastal area of Van Ly - Hai Hau in the rainy season.